Effect of Heavy Metal Polluted River Water on Body Weight and Hemoglobin Level in White Rats (Rattus novergicus) - Hendriyono, Franciscus Xaverius; Devi, Wivina Riza; Rosida, Azma; Hidayat, Taufiq (Berkala Kedokteran, 2024)
Contamination of heavy metal on the South Kalimantan River has become a well thrived issue. In the Barito River watershed, it is reported that there are heavy metals in the form of Pb, Hg and Cd. Heavy metals can affect physiological anatomical changes and the hematopoietic system. This study aims to determine the impact of heavy metal contamination on changes in body weight and hemoglobin levels. The research method is a true laboratory experiment using a pre-post-test group design. The subjects used were healthy male white rats (Rattus norvegicus), aged 2-6 months and weighing 250-300 gr. The research group was divided into two groups, the control group (K) was a group of experimental animals that were given distilled water while the treatment group (P) was a group of experimental animals that were given water contaminated with heavy metals (Pb, Cd, and Hg) ad libitum for 30 days. The results showed that there was no effect of giving Pb metal; 0.01 mg/l = 0.006 mg/kgBW, Cd; 0.003 mg/l = 0.018 mg/kgBW, Hg; 0.001 mg/l = 0.0006 mg/kgBW and Pb+Cd+Hg; 0.006 mg/kgBB + 0.018 mg/kgBB + 0.0006 mg/kgBB on body weight of white rats. There was a significant decrease in Hb levels in white rat hemoglobin after administration of Pb metal; 0.01 mg/l = 0.006 mg/kgBB. Pb metal in water can influence changes in decreasing Hb levels during sub-acute administration. It can be concluded that there was a significant difference in hemoglobin levels before and after giving water containing Pb/lead metal, whereas in the other groups there was no significant difference, as did the Hb levels.